25.4: Laser‐Excited Phosphor/Dye in Liquid for High‐Power Digital Projectors. Issue 1 (June 2015) - Li, Kenneth
Abstract : Laser excited phosphor has been used to excite phosphor material, producing high intensity light output with smaller etendue than that of LEDs with the same long lifetime. Due to the difficulty of heat dissipation in using standard phosphor wheel configuration, the output of such projectors are limited to upper limit in the range of 6, 000 lumens to 12, 000 lumens. This paper describes the used of circulating liquid with a suspension of phosphor powder in an optical cell. When the phosphor particles in liquid are excited by the laser, a visible light with certain bandwidth is generated. Since each phosphor particle is surrounded by liquid, the heat sinking issues are eliminated. To provide high illumination efficiency, multiple types of phosphor can be used with different center wavelengths such that the proper output spectrum can be obtain. To add further flexibility, dye can be used in addition to phosphor give further flexibility to the choice of materials providing the desired output light spectrum. Using this technology, projector output can be extended to beyond 30, 000 lumens for standard digital cinema and beyond 60, 000 lumens for 3D digital cinema.